Woodstove exposure as a risk factor for airway obstruction - Alexandros Mpagordakis; Aristea Pasa; Argiro Troullinou; Styliani Stratidaki (Ene, 2015)
Background: The recent financial crisis in Greece has significantly increased woodstove use and therefore the indoor air pollution of the household atmosphere. Related studies have shown that indoor air pollution is associated with the onset of obstructive airway diseases, especially in women who are occupied with household duties. Aim: To investigate whether the woodstove exposure is a risk factor of obstructive airway disease especially in nonsmoking women. Methods: In this cross-sectional study participated 410 individuals (51.7% women, mean age 56,1 ± 13,0 years, ranging from 40 to 93 years old) who visited eight Primary Health Care Settings on the island of Crete, Greece. A spirometry testing was performed to assess the degree of airflow limitation setting criteria the fixed ratio of spirometry values (FEV1 / FVC <70%), while the existence of possible Chronic Obstructive Pulmonary Disease (COPD) was assessed using the International Primary Care Airways Group (IPAG) scale. The degree of woodstove exposure was estimated: in years, months per year and hours per day. The degree of the effect of factors related to COPD development was tested by multiple logistic regression and presented as adjusted odds ratio. P-value <0.05 were considered statistically significant. Data were analyzed using the IBM SPSS Statistics version 22. Results: Airflow obstruction was diagnosed in the 13.7% of the study participants and was associated with the woodstove exposure (86.8 and 88.2, p = 0,009) between those exposed and non-exposed (participants) respectively. However, multivariate analysis revealed that this association was not significant (87.4 vs. 88.2, p=0.097) after adjusting for patients characteristics, suggesting that airflow obstruction did not differ between exposed and non-exposed participants. We also found that Chronic Obstructive Pulmonary Disease (COPD) [IPAG>17] were establish in non-smoker women who were exposed for 30.2 years to woodstove smoke compared to non-COPD non-smoker women (11.8 years exposure), despite the fact that interactions terms (female gender, smoking, woodstove use, cough with sputum production) were not associated with COPD development. Conclusion: The present study confirms that woodstove exposure (about 30 years) is associated with Airway Obstruction in non-smoker women. Also, a greater woodstove exposure is indicative of a greater prevalence of airflow limitation and a greater COPD-related symptoms.